Environmental stressors perceived by patients in the surgical intensive care unit and their level of satisfaction with nursing care - Hacer Karaer; Esma Ozsaker (Journal of Perioperative Nursing)
Purpose: The purpose of this study was to determine environmental stressors perceived by patients in the surgical intensive care unit and their level of satisfaction with nursing care.